Cloning and Partial Characterization of a Cold Shock Domain‐Containing Protein Gene from the Dinoflagellate Scrippsiella trochoidea. (29th August 2018) - Deng, Yunyan; Hu, Zhangxi; Chai, Zhaoyang; Tang, Ying Zhong
Abstract: CSPs, cold shock domain (CSD) containing proteins, are demonstrated to be involved in low temperature responses and various cellular processes under normal growth conditions. Here, we used the cosmopolitan, toxic, and resting cyst‐producing dinoflagellate Scrippsiella trochoidea as a representative harmful algal bloom‐forming dinoflagellate to investigate the expression patterns of CSP in vegetative cells in response to temperature shocks and in resting cysts, with an objective to probe the possible function of CSP in dinoflagellates. The full‐length cDNA of a CSP gene from S. trochoidea ( StCSP ) was obtained which has a solely N‐terminal CSD with conserved nucleic acids binding motifs. The qPCR results together indicated StCSP expression was not modulated by temperature at the transcriptional level and implied this gene may not be associated with temperature stress responses in S. trochoidea as the gene's name implies. However, we observed significantly higher StCSP transcripts in resting cysts (newly formed and maintained in dormancy for different periods of time) than that observed in vegetative cells (at exponential and stationary stages), indicating StCSP is actively expressed during dormancy of S. trochoidea . Taking together our recent transcriptomic work on S. trochoidea into consideration, we postulate that StCSP may play roles during encystment and cyst dormancy of the species.